ANALISIS KEMAMPUAN PSIKOMOTORIK DALAM PRAKTIKUM BIOKIMIA PERCOBAAN LIPID PADA MAHASISWA PROGRAM STUDI PENDIDIKAN KIMIA UNIVERSITAS MUHAMMADIYAH PONTIANAK - Atrisman Atrisman; Hairida Hadiarti; Fitriani Fitriani (Jurnal Ilmiah Ar-Razi, 2017)
ABSTRACTThis study aimed to describe the students’ psychomotor skills in Biochemistry Lab of Lipid Determination of Saponification Number in even semester in Academic Year 2014/2014. Using descriptive method, this study employed the entire students who took Biochemistry Lab course. The instruments used were observation and psychomotor-based interview. The study revealed that the students’ average score of each psychomotor aspect was 85.2%, the practical tool usage aspect was 83.93%, the practical tools stringing aspect was 92.56%, the experimental treatment observation aspect was 86.36%, and the phasic experimental performance aspect was 86.36%. As a result, it can be concluded that that the students of Chemistry Education have excellent psychomotor skills with the overall average score of psychomotor aspect of 86.27%.Keywords: descriptive, psychomotor skills, Biochemistry experimental